To What Extent Do Online News Platforms Frame Environmental Issues? A Content News Analysis In Indonesia's Dompu Maize Development Program - Baskoro Wicaksono; Al Fauzi Rahmat; Fajar Rahmanto; M. Rafi; Lóránt Dénes Dávid (Nyimak: Journal of Communication)
This article examines how online news frames environmental issues in the corn development program in Dompu, West Nusa Tenggara, Indonesia. Furthermore, this article uses qualitative-exploratory research to analyze the news content with the analytical knife of Robert M. Entmen's framing model. Then, the data analysis tool uses NVivo 12 Plus to code the data and distribute terms and words that correlate with the framing of online news. The findings showed that certain aspects of the maize development program were more prominent, in general, the national online media emphasized elements of “make moral judgment” and “treatment recommendation”. In contrast, the local online media emphasized “define problem” and “diagnose cause”. Both online media explicitly instructed how environmental issues in Dompu Regency are important for environmental journalists. Thus, this implies differences in framing between national and local online media, and illustrates that environmental journalists have an important role in framing environmental issues.